Controlled Dispersion Of Clays And Its Effects On Phosphate Clay Waste Dewatering - D. M. Deason; G. Y. Onoda (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
Phosphate clay wastes, as currently produced, leave montmorillonite clay in a highly dispersed and disintegrated form. Alternative processing, where the extent of swelling and self-disintegration of such clays is controlled or limited, may result in improved settling and consolidation behavior. In this study, a method to control montmorillonite dispersion, through preservation of clay tactoids, was examined. Through this process, significant improvements in settling rates and sediment solids concentrations were achieved in both pure clay systems and on simulated phosphate clay wastes.